2005
DOI: 10.1016/j.ijindorg.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Intermediation in innovation

Abstract: The paper offers a new theoretical framework to examine the role of intermediaries between creators and potential users of new inventions. Using a model of universityindustry technology transfer, we demonstrate that technology transfer offices can provide an opportunity to economize on a critical component of efficient innovation investments: the expertise to locate new, external inventions and to overcome the problem of sorting 'profitable' from 'unprofitable' ones. The findings may help explain the surge in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 25 publications
(33 reference statements)
1
66
1
1
Order By: Relevance
“…Hanft and Korper (1980) have found that societal side effects, in terms of the use of scarce resources, may outweigh the benefits of an innovation. Similarly, Gerwin and Tarondeau (1982), Walton et al (2002), Hoppe and Ozdenoren (2005) and Portzsolt et al (2009) have found out that the benefits of innovation remain often, if not undesirable, at least obscure.…”
Section: Consequence Uncertaintymentioning
confidence: 99%
“…Hanft and Korper (1980) have found that societal side effects, in terms of the use of scarce resources, may outweigh the benefits of an innovation. Similarly, Gerwin and Tarondeau (1982), Walton et al (2002), Hoppe and Ozdenoren (2005) and Portzsolt et al (2009) have found out that the benefits of innovation remain often, if not undesirable, at least obscure.…”
Section: Consequence Uncertaintymentioning
confidence: 99%
“…Nevertheless, the discussion on external knowledge complementarities and firm-level innovation can be summarized in the hypothesis that the deployment of external knowledge should be positively associated with innovation performance (Nooteboom et al, 2007). This hypothesis is supported in different strands of the literature, including marketing (Gemünden et al, 1996), innovation systems (Edquist, 1997;Freeman, 1995;Lundvall, 1992), business management (Jaruzelski and Dehoff, 2007) and several areas of economics and policy research (de Man and Duysters, 2005;Dodgson, 1993;Drejer and Holst Jørgensen, 2005;Frenz and Letto-Gillies, 2009;Hagedoorn, 2002;Håkansson, 1989;Hoppe and Ozdenoren, 2005;Mention, 2011;Panda and Ramanathan, 1996 Mention (2011) and Tether (2002) suggest that cooperation with universities and research organizations has a positive influence on more radical forms of innovation, other studies, such as that by Frenz and Letto-Gillies (2009), suggest that cooperation is much less useful than in-house efforts.…”
Section: Jena Economic Research Papers 2012 -037mentioning
confidence: 99%
“…As innovation processes are generally associated with uncertainty along both market and technology dimensions (Hoppe and Ozdenoren 2005;Macho-Stadler et al 2007), it is difficult to know what mechanisms best cater to this process. In the specific case of AE, contextual factors might play an important role in determining the outcome of a particular initiative (Henrekson and Rosenberg 2001).…”
Section: Public Choice Policy Robustness and Policy Interventionsmentioning
confidence: 99%
“…The same researchers also found that older TTOs seem to be less efficient, suggesting an absence of learning effects, or even negative learning. Moreover, the complexity of the entrepreneurial environment and the number of possible choices and strategies can often lead to the failure of TTOs (Hoppe and Ozdenoren 2005). While effective AE initiatives may rely on TTOs, the critical boundary condition is not the presence of a TTO per se but the degree to which the TTO complements the researcher in some crucial dimension.…”
Section: Tto and Its Capabilitiesmentioning
confidence: 99%